Statistics and Policy Decisions: Issues in Statistical Analyses - Kraemer, Helena Chmura (International Journal of Statistics in Medical Research, 2015)
When national policy decisions are to be guided by the results of statistical analyses, it is important, to avoid being misled to look beyond the authors’ conclusions and first to assess the study design, measurement and analytic methods, in order to decide whether a study’s conclusions rest on a solid foundation. In particular, observational studies must be carefully and critically evaluated. Using a study widely cited concerning the effects of low-level lead exposure and IQ, we illustrate several methodological errors, long known but often ignored. The goal is not to settle the controversies about the effect of lead on IQ, nor to disparage observational studies, for they are the foundation of all studies done to guide policy, but to encourage additional care in the use of such studies to address policy questions.